Weak ferromagnetism in poly(3-methylthiophene)(PMTh) - Correa, A. A.; Walmsley, L.; Bulhoes, LOS; Ortiz, W. A.; de Oliveira, AJA; Pereira, E. C. (Elsevier B.V., 2001)
Ferromagnetic behaviour at 300 K has been observed from SQUID experiments in ClO4- doped PMTh, the samples were prepared electrochemically at 25 degreesC in acetonitrile with 0.1M LiClO4 and then partially reduced. Atomic absorption analysis discards magnetic particles contamination. Hysteresis curves were observed for pressed pellets in ail range of temperatures (300K-2K). The remanence at 300 K and pressed at 250 bar was around 8.06x10(-4) emu/g with coercitivity of 130 Oe. The influence of water content in the solvent during the sample synthesis and the pressure is shown. We discuss a model that explains our data in terms of the anisotropic superexchange Dziatoshinski-Moriya interaction giving rise to weak ferromagnetism.
Keywords: magnetic measurements; polythiophene and derivatives; electrochemical polymerization; electrochemical doping